SIMULATION OF GROUNDWATER FLOW USING SOFTWARE MODFLOW BASED ON RAINFALL - MONIKA PASARIBU , JUNITA
Water playing apart as an important element in human live, because water is the new natural resource and play apart of supplying various need. In this final project conducted modeling groundwater flow using Software MODFLOW based on rainfall and estimate the water optimum which can be taken away from study location without causing degradation of groundwater surface. Analysis that used to know about the amount of groundwater supply potention is hydrometeorology F.J Mock method. Based on calculation, the amount groundwater potention are about 60.069 million m3/year with each average groundwater supply in wet months are about 6.119 milion m3/month and dry months are about 1.667 miilion m3/month. Simulation of groundwater flow done by using Software MODFLOW 3.1 constituted by Darcy's Law, where from simulation obtained a model with direction and velocity of groundwater flow that move toward East and West from the top of Kendang Mountain follow the topography pattern which trend to heel of each direction. Obtained also the result of simulation showing that if we do pumping of groundwater using 3 sample well pump with the debit of each well pump about 18 lt/second/well not causing degradation of groundwater suface. Hence maximum intake of groundwater from study location can be adapted with groundwater supply in wet months and dry months.